Psychiatric morbidity among women in Norwegian prisons, 2010–2019: a register-based study - Vegard G Svendsen; Marianne Riksheim Stavseth; Torbjørn Skardhamar; Anne Bukten (BMC Psychiatry)
Abstract Purpose Research suggests that women in prison have more mental health problems than men and are prone to suffer from more severe psychiatric disorders. This study utilizes national registry data to describe demographic and psychiatric gender differences in Norwegian prisons, and to investigate comorbid psychiatric disorders and time trends in psychiatric morbidity among women. Methods Longitudinal data from the Norwegian Prison Release Study linked with the Norwegian Patient Registry and data from Statistics Norway provided information on health care utilization, socioeconomic status, and history of psychiatric disorders among all individuals (nwomen = 5,429; nmen = 45,432) who were incarcerated in a Norwegian prison between 2010 and 2019. Results Women were more likely than men to have a history of any psychiatric disorder (75% vs. 59%). Substance use disorders and dual disorders were highly prevalent in both genders, yet highest among women (56 and 38% respectively, versus 43 and 24% among men). From 2010 to 2019, we found a considerable increase in the 12-month prevalence of most diagnostic categories among women entering prison. Conclusion Psychiatric and dual disorders are highly prevalent in Norwegian prisons, and especially among women. The proportion of women entering prison with a recent history of mental health problems has increased rapidly over the last decade. Women’s prison institutions need to adjust health and social services, and awareness about substance use and other psychiatric disorders in order to meet the increasing proportion of women facing these challenges.